Laboratory Maintenance and Culturing of the Nematode‐Trapping Fungus Arthrobotrys oligospora. Issue 2 (5th February 2021) - Lin, Hung‐Che; Hsueh, Yen‐Ping
Abstract: Nematode‐trapping fungi (NTF) and nematodes are common and sympatric in nature. The molecular basis that underlies this interkingdom predator–prey interaction remains largely uncharacterized. Both NTF and nematodes can be easily isolated from soil samples. NTF do not form traps in nutrient‐rich environments, yet trap morphogenesis can be observed under nutrient‐poor conditions and upon simultaneous sensing of the nematode cues. Here, we present protocols for laboratory maintenance and culturing of the model NTF Arthrobotrys oligospora . © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Growth of nematode‐trapping fungi on solid medium Basic Protocol 2 : Growth of nematode‐trapping fungi in liquid medium Basic Protocol 3 : Collection of conidia from solid medium Support Protocol 1 : Preparation of Miracloth filter funnel Basic Protocol 4 : Induction of trap morphogenesis Alternate Protocol : Quantitative measurement of trap induction Support Protocol 2 : Preparation of synchronized C. elegans L4 Basic Protocol 5 : Establishing C. elegans survival rate upon exposure to A. oligospora Basic Protocol 6 : Storage of nematode‐trapping fungi strains